Unlocking Students’ E-Wallet Adoption: The Roles of Service Features, Security, and Ease of Use - Ahmad Junaidi; Muh Hamzah (Growth: Journal Management and Business, 2026)
The rapid advancement of financial technology (fintech) has accelerated the adoption of electronic wallets (e-wallets) as one of the most widely used digital payment instruments among university students. However, users' intention to adopt e-wallets is influenced by various factors related to service quality and application characteristics. This study aims to examine the effects of service features, security, and perceived ease of use on the intention to use e-wallets among students of Universitas Nurul Jadid. This research employed a quantitative approach with an associative research design. Primary data were collected through questionnaires distributed to 246 respondents selected using a purposive sampling technique. Data were analyzed using multiple linear regression with the assistance of SPSS software, following validity, reliability, and classical assumption tests. The results indicate that, partially, service features (t = 6.499; p < 0.001), security (t = 5.917; p < 0.001), and perceived ease of use (t = 3.277; p = 0.001) have a positive and significant effect on the intention to use e-wallets. Simultaneously, the three independent variables also have a significant effect on the intention to use e-wallets, with an F-value of 227.544 (p < 0.001). Furthermore, the coefficient of determination (R²) of 0.738 indicates that 73.8% of the variance in e-wallet usage intention can be explained by service features, security, and perceived ease of use, while the remaining 26.2% is explained by other factors outside the proposed model. These findings suggest that improving service features, strengthening security systems, and enhancing application usability are essential strategies for increasing university students' intention to adopt e-wallets as a digital payment method. The study contributes to the digital payment adoption literature by demonstrating that technology-related convenience alone is insufficient to explain adoption intention and that functional service features and perceived security should be considered alongside ease of use when explaining e-wallet acceptance among university students.